Pengaruh Profitabilitas, Solvabilitas, dan Aktivitas Persediaan terhadap Audit Delay pada Perusahaan Retail yang terdaftar di Bursa Efek Indonesia Periode 2014-2015 - Debbianita -; Vinny Stephanie Hidayat; Ivana - (Jurnal Akuntansi, 2017)
AbstractThe aim of this research is to determine the effect of profitability, solvability, and inventory activity toward the Audit Delay on retail companies that are listed in Indonesia Stock Exchange. The population of this research is whole of the retail companies that are listed in the Indonesia Stock Exchange in 2014-2015. The method used in this research is explanatory research, and the sampling method used was judgement sampling method. Research hypothesis testing using T test, F test, and multiple regression analysis using SPSS version 20.0. The results show that profitability, solvability, and inventory activity have no effect on audit delay on retail companies that are listed in Indonesia Stock Exchange.Keywords: Audit Delay, Â Inventory Activity, Profitability, and SolvabilityÂ